Respostas

A melhor resposta!
2013-10-30T12:52:28-02:00
/\=b²-4.a.c
/\=(-2)²-4.(1).(-48)
/\=4+192
/\=196
x=-b +- raiz de delta
              2.a 
x=-(-2) +- raiz de 196
                2.1
x=2+- 14 
        2 
x¹= 2+14 = 16 = 8 
         2        2 
x²=2-14 = -12 =- 6 
      2        2 
2 5 2
2013-10-30T13:00:38-02:00
X²-2x-48
a=1
b=-2
c=-48
Δ =b²-4.a.c
Δ =(-2)²-4.(1).(-48)
Δ =4+192
Δ =196

x=-b±√ Δ/2a
x=-(-2)±√196/2(1)
x=2±14/2
x'=2+14/2
x'=16/2
x'=8

x''=2-14/2
x''=-12/2
x''=-6

Espero ter ajudado....;D
Não se esqueça de classificar a melhor resposta.Grata.
1 5 1